The Application of Continuum Model in Simulating Char Fragmentation and Residual Ash Formation. Issue 4 (3rd April 2017) - Du, Qian; Su, Lipeng; Yuan, Pengfei; Li, Huiyi; Gao, Jianmin; Zhao, Zhifeng; Dong, Heming; Wu, Shaohua
ABSTRACT: The monosized spherical model was established originally to study the process of char combustion and residual ash formation. On this basis, a modified spherical model was obtained by introducing the multi-size mineral inclusions and pores to the spherical char. The results show that the surface ash mean size is proportional to the mineral volume fraction in monosized model. In addition, a significant bimodal characteristic occurs on the distribution curve of isolated ash mean size in cases of large porosity and pore size, which is in good agreement with experiment results. As a contrast, the planar model is more beneficial to form a large number of small isolated ash particles, whereas the mineral inclusions in monosized spherical model are inclined to coalesce into a large surface ash particle eventually. As regards the modified spherical model, the separation effects of both small and large surface ash particles can be strengthened with respect to number density. It can be expected that the modified model is more aligned with the actual conditions.